STUDY OF CHLORIDE PENETRATION AND SULFATE RESISTANCE ON ORDINARY PORTLAND CEMENT (OPC) CONCRETE WITH GROUND GRANULATED BLAST FURNACE SLAG (SLAG CEMENT) - Pratama Syahputra, Anggi
Research on the effect of Ground Granulated Blast Furnace Slag (GGBFS) on durability properties has been carried out. GGBFS products from PT Kerakatau Semen Indonesia are used as Supplementary cementitious materials (SCMs) in Portland cement type-1 with variations of GGBFS in the mixture, namely 0% (control), 25%, 50) %, and 70%. For each mixture, a compressive test, RCPT, and expansion due to sulfate were carried out. Specifically for the RCPT test results, the software life-365 was used to help analyze the period of chloride initiation into concrete assumed to be on the construction slab of coastal buildings (jetty). The control character with the lime water curing method is up to 90 days, the compressive strength of cylindrical concrete at the age of under 28 days is lower in all varieties, however, it is obtained that the compressive strength is higher at the treatment age above 28 days. days, the compressive strength of cylindrical concrete at the age of under 56 days is lower in all variations but the compressive strength is obtained l it is higher at the treatment age of concrete above 56 days with a GGBFS variation of 25%. The addition of GGBFS causes a decrease in the expansion properties due to sulfates. The addition of GGBFS also causes a decrease in the value of RCPT so that the diffusion of chloride in concrete is getting smaller which can increase the service life of building construction exposed to chloride, besides that the decrease in the value of chloride diffusion is getting smaller along with the length of the curing period.